Customer satisfaction: the impact of revamping HAI Magazine published by Utusan Melayu (Malaysia) Berhad among customers in Klang Valley / Afdal Shahizad Zainudin - Zainudin, Afdal Shahizad (Faculty of Business and Management, 2007)
Nowadays, there are many competitors in the Malaysian magazine industry. Readers are given choices to choose their reading material for the magazine. The dailies range from Bahasa, Chinese, Tamil and English are competing amongst themselves to get the new readers.